2017
DOI: 10.1111/acer.13474
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Mediated Missplicing of Mcl-1 Pre-mRNA is Involved in Neurotoxicity

Abstract: Background Heavy and chronic ethanol (EtOH) exposure can cause significant structural and functional damage to the adult brain. The most devastating consequence of EtOH exposure is the neurotoxicity associated with the depletion of neurons. Regulation of splice variants in the brain can modulate protein functions, which may ultimately affect behaviors associated with alcohol dependence and EtOH-mediated neurotoxicity. Since alcohol consumption is associated with neurotoxicity, it is possible that altered splic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
1
15
1
Order By: Relevance
“…These differences in Mcl-1L expression could be related to the differences in its stability or half-life across the cell types. In line with our previous report 24 , EtOH exposure caused a dramatic reduction in SRSF1 protein levels in hNSPs, hNPCs, and immature neurons. Interestingly, SRSF1 levels in mature neuron cultures were slightly reduced but maintained in cells exposed to EtOH suggesting that its expression levels were sufficient to maintain Mcl-1L splicing over Mcl-1S.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These differences in Mcl-1L expression could be related to the differences in its stability or half-life across the cell types. In line with our previous report 24 , EtOH exposure caused a dramatic reduction in SRSF1 protein levels in hNSPs, hNPCs, and immature neurons. Interestingly, SRSF1 levels in mature neuron cultures were slightly reduced but maintained in cells exposed to EtOH suggesting that its expression levels were sufficient to maintain Mcl-1L splicing over Mcl-1S.…”
Section: Resultssupporting
confidence: 93%
“…However, little is known regarding the potential impact of alcohol on alternative splicing of genes during the fetal development and its involvement in the development of fetal alcohol spectrum disorder (FASD). We have recently shown that EtOH exposure of fetal neurons suppresses expression levels of serine/arginine rich splicing factor 1 (SRSF1) and causes missplicing of myeloid cell leukemia 1 (Mcl-1) by favoring the Mcl-1S splicing over Mcl-1L 24 . Several studies suggested that while the longer gene product Mcl-1L enhances cell survival by inhibiting apoptosis in response to various stress conditions in different cell types, the alternatively spliced shorter gene product Mcl-1S may promote apoptosis 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, EtOH has been proposed to affect the post-translational modification of proteins in non-metabolizing cells 53 , 54 that might also contribute to tBid-induced OMMP. Recently, Sariyer et al 55 showed that in neuronal cells chrEtOH exposure causes Mcl-1 missplicing and reduces the anti-apoptotic isoform of Mcl-1 but our data did not show this in HepG2 cells. The most relevant mechanistic finding here was that chrEtOH facilitated the tBid-induced Bak oligomerization that alone can explain the increased OMMP in HepG2 cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Since the inclusion of exon 3 of BIS mRNA is critically determined by SRSF3 levels, the maintenance of SRSF3 at the appropriate physiological levels is indispensable for the synthesis of intact BIS protein. Therefore, the change in BIS mRNA in linearity and subsequent outcome on cellular fate should be investigated for the conditions in which SRSF3 is reduced, or, alternatively, the conditions in which the spliced form of SRSF3 is increased, such as exposure to alcohol or oxidative stress [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%